(untitled) (Analele Universitatii din Bucuresti – Seria Istorie, 2024)
During the last two centuries of the Roman Republic the public building projects of the aristocrats as well as their private architectural accomplishments mirror the profound process of cultural exchanges that characterize the metamorphosis of the Roman world. Following this process and against the background of the generalized crisis of the Roman republic, the redefined discourse on power appropriates the architecture concept as a tool of communication. The paper aims to explore this meaningful relation of the Romans with the act of construction at the sunset of the Republic considering the Pompeian second style of painting as one of the artistic expressions of the elites’ agency.